2020
DOI: 10.32328/turkjforsci.711389
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Change of Chlorophyll Content (Spad Value) in Some Tree and Shrub Species

Abstract: A part of this study was previously presented as an oral presentation and published in the book of proceedings as full text at III. International Mediterranean Forest and Environment Symposium in Kahramanmaraş, Turkey in 2019.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…The amount of chlorophyll varies between species as well as within species according to subspecies, varieties, and forms (Canova et al 2008;Cetin 2017). It is known that one of the important factors determining the amount of chlorophyll is the leaf structure (Taner & Sade 2005;Atar et al 2020). In this study, chlorophyll contents were statistically very significant in hazelnut cultivars (p˂0.000).…”
Section: Chlorophyll Content (Spad Values)mentioning
confidence: 46%
See 1 more Smart Citation
“…The amount of chlorophyll varies between species as well as within species according to subspecies, varieties, and forms (Canova et al 2008;Cetin 2017). It is known that one of the important factors determining the amount of chlorophyll is the leaf structure (Taner & Sade 2005;Atar et al 2020). In this study, chlorophyll contents were statistically very significant in hazelnut cultivars (p˂0.000).…”
Section: Chlorophyll Content (Spad Values)mentioning
confidence: 46%
“…The highest chlorophyll content was detected in "Kuş", the lowest value was found in "Kargalak". Atar et al (2020) reported that C. avellana has 30.6-48.9 SPAD values.…”
Section: Chlorophyll Content (Spad Values)mentioning
confidence: 99%
“…Valuable information has been obtained in a few studies on this subject, and it has been determined that the movement of heavy metals within the plant varies depending on the plant variety and heavy metal. In studies conducted on annual rings, while Zn and Pb elements were replaced in Cedrus deodora, the Cu element was not displaced [40][41][42], the Ni element was limited [43,44], and Co was displaced in Cedrus atlantica [38], the Bi element is replaced in Cupressus arizonica, while the Cd and Ni elements are not [39], and Cd, Fe, and Al were not replaced in Corylus colurna [24] were determined by several research [44][45][46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…The lowest average values in June had seedlings of the "Rudnik" provenance, while in October the lowest average values had the "Grabova reka" provenance seedlings. Atar et al, (2020) investigated in their research the SPAD values of Quercus hartwissiana Steven species, in May and October, and obtained the average maximal SPAD value of 32.7 for May, and 28.8 for October. Jagiełło-Leńczuk et al (2015) reported maximal values for Common oak in mid-July, numbering 49.9 SPAD units, while the average value of measurements taken in the period from May to November was 31.8.…”
Section: The Average Spad Index Values In Junementioning
confidence: 99%